Health Promotion Of Covid-19 Vaccine At Health Department In Palu - Murni Kaddi, Sitti; Puspa Ningsih, Fitriani (International Journal of Educational Research & Social Sciences, 2021)
This study aims to describe and recognize health promotion about the benefits of the COVID-19 vaccine at the Palu City Health Departmen. The research method used is qualitative. The data source comes from in-depth observations and interviews. Data analysis techniques are data reduction, data presentation, and data verification. The results showed that there are three stages carried out by the government, namely advocacy related to government efforts to add public insight related to public policy on the covid-19 vaccine in Palu City. Communication can be done face-to-face and online media. The second stage, this social support comes from the police, Pamung Praja Police Unit, TNI, young people as ambassadors of covid-19, sub-district departmens to villages, medical personnel, media consisting of mass media, and social media used by the community, especially in Palu City.The third stage, community empowerment is a process of providing information to families or groups and individuals continuously and continuously. The information or message is very varied ranging from the use of raw Indonesian to the use of Kaili regional languages and languages that are often used every day by the people of Palu City. The delivery of the message uses face-to-face and media communication such as TVRI Central Sulawesi, local radio, FB, Instagram, Palu City Departmen website, Youtube, banners, and brochures.